THE INFLUENCE OF THREE-WEEK AEROBIC EXERCISE PROGRAM ON NEURODYNAMIC PARAMETERS OF PATIENTS UNDERWENT CORONARY BYPASS GRAFTING - Y. A. Argunova; O. A. Trubnikova; A. S. Mamontova; I. D. Syrova; I. N. Kuhareva; O. V. Maleva; O. L. Barbarash (Российский кардиологический журнал, 2016)
Aim. To assess the influence of three-week aerobic exercise program on the parameters of cognition status of patients underwent coronary bypass grafting (CBG).Material and methods. Totally, 92 men studied with ischemic heart disease (CHD), underwent CBG under on-pump. Patients were selected to 2 groups: first group — 39 patients (mean age — 55,5±5,3 y.) had a 3-week program of bicycle training, the second — 53 persons (57,2±6,21 y.) did not participate in bicycle trainings. The following neurodynamics parameters were evaluated — velocity of complex visualmotor reaction (VCVMR), level of functional mobility of neural processes (LFM) and endurance of the brain (EB) on 5-7 day before CBG, in 7-10 days and in 1 month after operation.Results. In assessment of the neurodynamics parameters in post-operation period, as on 7-10 day, there were no significant differences in the groups. On 7-10th day and in 1 month after CBG there was acceleration of sensomotoric reactions at neurodynamic tests comparing to preoperation values. In 1 month in patients without trainings there was reaction speed in neurodynamics tests comparing to those after bicycle trainings. Dynamics analysis of the mistakes done showed their increase in bicycle group on 7-10 day after CBG with further return to pre-operation levels by 1 month — in EB and LFM tests, but in the group without trainings there was increase by 7-10 day, as by 1 month after CBG. While comparing the quantity of skipped signals in non-training patients it was significantly higher than in bicycle group during the LFM and EB test.Conclusion. At the background of three-week bicycle training in patients underwent CBG, there is improvement of neurodynamics parameters, that does set the trainings as the method of prevention and rehabilitation of delayed cognitive dysfunction.